Identifikasi Path Pembentuk Citra Kota di Koridor Jalan Kemasan Kotagede Yogyakarta - Prasetyo Febriarto; Septi Kurniawati Nurhadi (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2024)
One of the important elements forming a city image is a path that creates connectedness and integration. Proof of Path quality research is by identifying paths, then correlating with the path city image theory and the physical quality theory of the city environment. The aim of this research is to identify the physical clarity of paths and the environment in the Kemasan road corridor, Kotagede, Yogyakarta. The research method uses an exploratory method with primary data collection techniques and secondary data which is then analyzed using an exploratory descriptive method which reports existing physical conditions related to paths and the physical quality of the environment and is correlated with related theories. The research findings show that the quality of the physical condition of the corridor influences the clarity of the path. The conclusion that has been obtained is that there are similar paths to the city image theory and the physical quality of the city environment at the research location where the path on Jalan Kemasan is clearly visible and strong. The physical quality of the city environment at the research location, namely the Kemasan road corridor, is clearly visible and influences the clarity of the path.